The Economic Philosophy of Micro-Credit System - MISHRA, Sudhanshu K. (Journal of Economic and Social Thought, 2016)
Abstract. This paper aims at locating the practice of micro-credit system into a larger theoretical canvas of economic theory and philosophy. A systems theoretic approach has been adopted. Emergence of the ‘excluded’ class has been explained with the help of the theory of feedback. Individuals have been assumed to be myopic, local optimizer and bounded rational. In this context, the empirical experiences have been viewed and assessed as to their outcomes. Keywords. Micro-credit system, economic theory, philosophy, systems theory, self-organizing systems, feedback, exclusion. JEL. O16, G21, E11, D63, D78.